Symbolic bordering: The self-representation of migrants and refugees in digital news. (3rd April 2017) - Chouliaraki, Lilie
ABSTRACT: In this article, I combine theorizations of the selfie as an aesthetic and technological practice of digital self-representation with a theatrical conception of spectatorship, inspired by Adam Smith, in order to argue that the selfie has the potential to operate as a significant ethico-political spectacle in the spaces of Western publicity. I exemplify my argument by using the remediation of migrant and refugee selfies in mainstream news as a case study of "symbolic bordering"—as a technology of power that couples the geopolitical bordering of migrants in the outskirts of Europe with practices of "symbolic bordering" that appropriate, marginalize, or displace their digital testimonies in Western news media.